Editorial (2020)
Saint Thomas University, Tunja Sectional, presents the JoumalPrincipia Iuris No. 32, in which topics of vital importan ce for legalprogress are developed, conceived from the social projection, andwith axiological and epistemological bases that contribute to thesolution of different disciplinary and interdisciplinary researchproblems.Toe researches of this edition cover a great content of social andlegal problems, both in a national and intemational context.On this occasion, the Joumal Principia Iuris, Serie 32, presentsarticles that address and deepen into important topics for law, suchas, control of conventionality, constitutional reform, guardianship,sustainable development, post-conflict, immigration, humanrights and free personality development.We highlight the permanent and inexhaustible effort of the juristsand contributors of this edition, and with its greatness, ali thescience of law also <loes it.